EFFECTS OF FINANCIAL TECHNIQUES ON AUTOMAKERS COMPANY (World Economics and Finance Bulletin, 2023)
The automotive industry should review its operations and strive to improve its cost management in this sector by reducing its production costs. Organizations are facing the challenge of adapting to the ever-changing and ever-evolving business environment for survival. On the one hand, competitive markets are on the rise. On the other hand, investor assemblies are putting pressure on managers to determine value and explain precise and transparent measurement criteria. As a result, organizations Consider and use traditional costing and performance measuring systems based on industry accounting. One of the most significant techniques that can help an organization improve its cost-based performance is goal-based costing. Many companies depend on their ability to maintain balance in the production flow and modify the production process based on customer demand in terms of cost improvement, quality and performance, timely delivery of goods and flexibility and price. Goalbased costing is the systematic system of determining production costs that drives companies to success and certain level of profitability based on the above criteria. Objective-based costing is one of the most powerful strategic tools that allows an organization to concomitantly find the 3D dimension of quality, cost and time, while controlling costs before they occur.
Keywords: Financial Techniques; Automakers Company